1997
DOI: 10.1076/ceyr.16.12.1198.5023
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive ocular perfusion apparatus measuring outflow facility

Abstract: Our perfusion apparatus is highly stable, sensitive, and capable of measuring subtle changes in outflow facility in vivo and in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
1
3
1
Order By: Relevance
“…The scaling relationship parallels differences in anterior chamber volume among these animals. 41 It is similar in scale but slightly smaller in value than prior measurements in rats ( C = 0.044 ± 0.010 μL/min/mm Hg 14 and 0.051 ± 0.010 μL/min/mm Hg 35 ). Both studies examined Lewis rats so the higher facility of this albino strain may reflect the absence of pigment granules, which can accumulate in the trabecular meshwork.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The scaling relationship parallels differences in anterior chamber volume among these animals. 41 It is similar in scale but slightly smaller in value than prior measurements in rats ( C = 0.044 ± 0.010 μL/min/mm Hg 14 and 0.051 ± 0.010 μL/min/mm Hg 35 ). Both studies examined Lewis rats so the higher facility of this albino strain may reflect the absence of pigment granules, which can accumulate in the trabecular meshwork.…”
Section: Discussioncontrasting
confidence: 42%
“…Other variations of the method directly measure flow with a flowmeter and use a gravity feed to eliminate the pump and control circuitry. 33 35 The mCP technique was found to produce equivalent results as the CF technique in half the time. Moreover, C estimates were very consistent and were validated by inserting a shunt of known conductance into the eye.…”
Section: Discussionmentioning
confidence: 97%
“…Feola et al [21] reported values of 21.2 [11.2, 40.0] and 26.1 [23.8, 28.7] nl�min -1 �mmHg -1 for young and middle-aged Brown Norway rats, respectively, while Ficarrotta et al [15] reported a value of 23 ± 2 nl�min -1 �mmHg -1 for retired-breeder Brown Norway rats. Facility values in this study (23 ± 4 nl�min -1 �mmHg -1 ) are within margin of error of their findings, and all are around two-fold less than reported values for albino rat species [37,38]. Moreover, repeated estimates of outflow facility in conscious rats exhibited similar variability as cited studies performed on different rats [15,21].…”
Section: Plos Onesupporting
confidence: 77%
“…The system was tested in the range of facilities relevant to human eyes (≈200 nl / min / mmHg ). Kee et al [ 34 ] proposed a modified version of this system in which a number of components added for accuracy were omitted in the interest of simplicity. They tested their system using rat eyes ( C ≈ 50 nl / min / mmHg ).…”
Section: Introductionmentioning
confidence: 99%